2014
DOI: 10.1242/jcs.146662
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular glycine receptor function facilitates glioma formation in vivo

Abstract: BSTRACTThe neuronal function of Cys-loop neurotransmitter receptors is established; however, their role in non-neuronal cells is poorly defined. As brain tumors are enriched in the neurotransmitter glycine, we studied the expression and function of glycine receptors (GlyRs) in glioma cells. Human brain tumor biopsies selectively expressed the GlyR a1 and a3 subunits, which have nuclear localization signals (NLSs). The mouse glioma cell line GL261 expressed GlyR a1, and knockdown of GlyR a1 protein expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…This metabolic adaption makes the highly malignant hypoxic GBM cells susceptible to efficient cellular glycine clearance, suggesting a novel therapeutic treatment route by forcing the toxic over‐accumulation of glycine in the cytoplasm . In addition, intracellular glycine receptor signaling has recently been shown to promote glioma formation, Pseudopalisades have increased expression of glucose uptake transporter 1 (GLUT1) as compared with parenchymal cells indicating elevated carbon nutrition in CSCs residing in that area . This study suggests a dependence on glucose during hypoxia; however, CSCs have also been shown to possess a high tolerance to glucose deprivation.…”
Section: Environmental Stress and Therapeutic Insults Alter Csc Metabmentioning
confidence: 80%
“…This metabolic adaption makes the highly malignant hypoxic GBM cells susceptible to efficient cellular glycine clearance, suggesting a novel therapeutic treatment route by forcing the toxic over‐accumulation of glycine in the cytoplasm . In addition, intracellular glycine receptor signaling has recently been shown to promote glioma formation, Pseudopalisades have increased expression of glucose uptake transporter 1 (GLUT1) as compared with parenchymal cells indicating elevated carbon nutrition in CSCs residing in that area . This study suggests a dependence on glucose during hypoxia; however, CSCs have also been shown to possess a high tolerance to glucose deprivation.…”
Section: Environmental Stress and Therapeutic Insults Alter Csc Metabmentioning
confidence: 80%
“…An increasing number of studies have suggested in addition that GlyRs are also expressed in supraspinal sites 5,6,[9][10][11]59,60 . Interestingly, recent immunocytochemical and gene expression studies have determined that α3GlyRs are expressed in brainstem, trigeminal ganglia, nucleus accumbens and the hippocampus 17,20,21,23,[59][60][61] . Despite the absence of specific pharmacological tools to identify α3GlyRs, the presence of functional α3-containing GlyRs in several CNS areas has been inferred by using mice lacking α3GlyRs.…”
Section: Discussionmentioning
confidence: 99%
“…The following primers were used for conventional and real‐time qPCR: GlyR α1 forward 5′‐CTGTTTGCCTGCTCTTCGTGT‐3′ and reverse 5′‐TGGGGAAACCGATGCGAGATA‐3′; GlyR α2A forward 5′‐ATCAACAGTTTTGGATCGGTCA‐3′, GlyR α2B forward 5′‐TCAACAGCTTTGGGTCAATAG‐3′ and GlyR α2 reverse 5′‐CCTTCAGCAACTTGTACTGG‐3′; GlyR α3 forward 5′‐TGGGTACACGATGAATGATCTC‐3′ and reverse 5′‐TTAGCCCTGTCGATGAAGACC‐3′; GlyR β forward 5′‐TGAGCAAGCAGATGGGAAAGG‐3′ and reverse 5′‐TAACGTTGAAGAACAAGAAGCAG‐3′ (Forstera et al . ). The following primers were used for real‐time qPCR: GlyR α1 forward 5′‐CTGTTTGCCTGCTCTTCGTGT‐3′ and reverse 5′‐TGGGGAAACCGATGCGAGATA‐3′, GlyR α2 forward 5′‐ATCAATGGGAAGGACATCAGGA‐3′ and reverse 5′‐GTTATCAGTGGTGACATCATGG‐3′; GlyR α3 forward 5′‐TGGGTACACGATGAATGATCTC‐3′ and reverse 5′‐TTAGCCCTGTCGATGAAGACC‐3′; GlyR β forward 5′‐ACGCAGCTAAGAAGAACACTGTGA‐3′ and reverse 5′‐CCAAGTTCCATTGTTGACTTCAATG‐3′ (Kuhse et al .…”
Section: Methodsmentioning
confidence: 97%